2020
DOI: 10.1007/s00586-020-06424-5
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the outcomes of surgical treatment of lumbar spinal stenosis—a prospective 5- and 10-year follow-up study

Abstract: Purpose In this prospective study, we aim to determine surgical outcomes in patients with lumbar spinal stenosis (LSS) 10 years after surgery. Methods The study population consisted of 96 LSS patients who underwent decompressive surgery, 72 of whom participated in the 10-year follow-up. The patients completed a questionnaire preoperatively and 3 months, 5 years, and 10 years postoperatively. Outcome measures were satisfaction with the surgical outcomes, the Oswestry Disability Index (ODI), the visual analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 20 The significant improvement five years later corroborates a 10-year cohort in Finland. 17 The latter also revealed that quality of life outcomes were not significantly different at five and ten years since the first surgery. This complements previous literature.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“… 20 The significant improvement five years later corroborates a 10-year cohort in Finland. 17 The latter also revealed that quality of life outcomes were not significantly different at five and ten years since the first surgery. This complements previous literature.…”
Section: Discussionmentioning
confidence: 87%
“… 11 , 12 Many studies abroad have evaluated the quality of life of patients after surgery for LSS both in short (1 year) and long term (5 years and above). 6 , 7 , 13 , 14 , 15 , 16 , 17 In Africa, a plethora of studies have evaluated the epidemiological, clinical and therapeutic aspects of LSS. 9 , 18 , 19 , 20 , 21 Studies conducted in Cameroon and others sub Saharan African countries showed that LSS affects a younger population (40–60 years) compared to Western countries (65–70 years) and thus, incapacitates people who are still in the working population.…”
Section: Introductionmentioning
confidence: 99%
“…lumbar decompression surgery have been reported previously for comparative purposes. 16),19) Specifically, studies have reported a 40-55% JOA recovery rate 10 years after surgery, 11), [19][20][21][22][23][24] lumbar VASs of 30-35 mm, [19][20][21][22] ODIs of 25%-35%, and mean patient satisfaction of 7.0-8.0 points [20][21] following conventional lumbar decompression.…”
Section: Discussionmentioning
confidence: 99%
“…We used either Pearson’s r correlation or Spearman’s rank-order correlation to measure the correlation between two continuous variables. The 3-, 5-, and 10-year prognosis were taken as follow-up nodes ( Hassanzadeh et al, 2017 ; Tuomainen et al, 2020 ; Berberi, 2021 ). The comparison of a continuous variable in two or more than two groups was made using either a parametric test (Student’s t -test or analysis of variance) or non-parametric test (Wilcoxon rank-sum test or Kruskal–Wallis test) if the variable was normally distributed.…”
Section: Methodsmentioning
confidence: 99%